PENGEMBANGAN KOMIK DIGITAL BERBASIS MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KARAKTER KEJUJURAN SISWA KELAS III SD - Dewi Noviani, Luh; Desia Tristiantari , Ketut; Herya Darma Utami , Ketut (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop digital comic-based learning materials using the Problem-Based Learning (PBL) model to foster honesty in third-grade elementary school students. This is a research and development (R&D) study using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). Data collection utilized questionnaires and tests (compilation of pre-test and post-test scores). The results of content expert validation showed a percentage of 87.1% (Highly Acceptable), while media expert validation reached 93.1% (Highly Acceptable). The practicality test based on teacher feedback indicated a practicality level of 96% (Highly Practical). Based on the effectiveness test using a paired sample t-test, a significance value of 0.000 (< 0.05) was obtained, with an increase in the average score from 33 (pre-test) to 51.78 (post-test). The conclusion of this study is that the PBL-based digital comic medium is valid, practical, and effective in improving the honesty character of third-grade elementary school students.